Blue high borosilicate glass and preparation method thereof

Modified colorants are prepared by mesoporous silica encapsulating cobalt blue material and combining with silane coupling agent and boric acid ester, which solves the problems of colorant volatility and waste of boron components in blue borosilicate glass, achieving a more uniform and stable color and higher mechanical properties and heat resistance.

CN119683855AActive Publication Date: 2025-03-25HUAILAI TIANYUAN SPECIAL TYPE GLASS

Patent Information

Application Number
CN202510214128.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-03-25
Estimated Expiration
2045-02-26

AI Technical Summary

Technical Problem

In the prior art, the colorant of blue borosilicate glass is prone to evaporation during the high temperature melting stage, resulting in uneven color distribution, affecting the stability and quality of the product; at the same time, the volatility of boron components increases production costs and affects the mechanical properties of the glass.

Method used

The composite material is prepared by encapsulating the cobalt blue material by mesoporous silica, and combining it with silane coupling agent and borate ester to produce a modified colorant for the preparation of blue borosilicate glass. This method can prevent the volatilization of the colorant, improve color uniformity and stability, and enhance the mechanical properties and heat resistance of the glass.

Benefits of technology

The color uniformity and stability of blue borosilicate glass is achieved, which reduces the volatility of boron, improves the mechanical properties and heat resistance of the glass, reduces production costs, and improves the quality of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to blue high borosilicate glass and a preparation method thereof, and belongs to the technical field of glass manufacturing, and the blue high borosilicate glass comprises the following raw materials in parts by weight: 50-60 parts of silicon dioxide, 10-15 parts of boron oxide, 2-3 parts of aluminum oxide, 6-8 parts of alkali metal oxide, 3-4 parts of a compound clarifying agent and 1-3 parts of a modified coloring agent. According to the technical scheme, the cobalt blue pigment is coated with mesoporous silica, and the composite material is obtained; combining the composite material with a silane coupling agent to obtain a silanized composite material; combining the silanized composite material with boric acid ester to obtain a modified coloring agent; the prepared modified coloring agent enables the high borosilicate glass to have remarkable blue color and to be stable in color and not prone to volatilization under high-temperature and high-pressure conditions, the added composite clarifying agent is formed by mixing cerium dioxide, sodium sulfate and tin oxide, the clarity of the glass is improved, volatilization of boron is effectively reduced, and the service life of the glass is prolonged. The mechanical property and the stability of the high borosilicate glass are generally improved, and the quality of the glass is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass manufacturing, and in particular relates to a blue high-borosilicate glass and a preparation method thereof. Background Art

[0002] High borosilicate glass is a kind of tempered fire-resistant glass that effectively reduces the expansion coefficient of glass by changing the glass composition, effectively improves the light transmission performance and glass strength, glass softening point temperature, and glass thermal conductivity. The main components of high borosilicate glass are boron trioxide and silicon dioxide. Due to its excellent performance, it is widely used in aviation, instruments, lighting, fire protection, tableware and other fields. With the improvement of people's living standards, colored glass has attracted more and more attention. For example, blue high borosilicate glass is made by adding specific colorants (such as cobalt, iron and other metal oxides) to high borosilicate glass. This glass not only inherits the excellent physical and chemical properties of high borosilicate glass, but is also widely used in many fields because of its unique blue appearance.

[0003] In the prior art, when preparing blue high borosilicate glass, the colorant in its components is easily volatilized during the high-temperature melting stage, resulting in uneven color distribution of the high borosilicate glass, affecting the final color and stability of the product; and the traditional blue high borosilicate glass contains a large amount of boron, although its expansion coefficient is reduced, boron will volatilize to a certain extent during the melting and clarification process, resulting in a waste of boron raw materials and an increase in production costs. At the same time, it will also cause changes in the mechanical properties and process properties of the high borosilicate glass, affecting the final quality of the product. Summary of the invention

[0004] The purpose of the present invention is to provide a blue high-borosilicate glass and a preparation method thereof. A composite material is obtained by wrapping a cobalt blue material with mesoporous silica. The cobalt blue material is synthesized from cobalt chloride, aluminum chloride and a surfactant by a hydrothermal method. The cobalt blue material is wrapped with mesoporous silica to prevent the volatilization of the cobalt blue material during high-temperature calcination, and the color presented by the high-borosilicate glass can be more uniform and the stability can be better, thereby further enhancing the mechanical properties and thermal stability of the high-borosilicate glass. The composite material is combined with a silane coupling agent to obtain a silylated composite material. The silane coupling agent is grafted onto the surface of the composite material to improve the dispersibility of the composite material and increase its compatibility with other components in the high-borosilicate glass. The silylated composite material is combined with boric acid ester to obtain a modified colorant. The boric acid ester can enhance the heat resistance and stability of the high-borosilicate glass. , and can increase the boron content in the high borosilicate glass components and reduce the volatilization of boron. The borate ester is combined with the silanized composite material to further enhance the mechanical properties, heat resistance and stability of the high borosilicate glass. The prepared modified colorant can not only make the high borosilicate glass appear blue, but also has stable color under high temperature and high pressure conditions, and is not easy to fade and volatilize. Silicon dioxide, boron oxide, aluminum oxide, alkali metal oxide, composite clarifier and modified colorant are mixed, ball milled, melted at high temperature, clarified and homogenized, annealed, and cooled to obtain blue high borosilicate glass. The added composite clarifier has a good clarification effect, can eliminate tiny bubbles in the glass, improve the clarity of the glass, and effectively reduce the volatilization of boron. The blue high borosilicate glass prepared at last has good stability and mechanical properties, while reducing the production cost and improving the quality of the high borosilicate glass.

[0005] Technical problem to be solved by the present invention: In the prior art, when preparing blue high borosilicate glass, the colorant in its components is easily volatilized during the high-temperature melting stage, resulting in uneven color distribution of the high borosilicate glass, affecting the final color and stability of the product; and the traditional blue high borosilicate glass contains a large amount of boron, although its expansion coefficient is reduced, boron will volatilize to a certain extent during the melting and clarification process, resulting in a waste of boron raw materials and an increase in production costs. At the same time, it will also cause changes in the mechanical properties and process properties of the high borosilicate glass, affecting the final quality of the product.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A blue high borosilicate glass comprises the following raw materials in parts by weight: 50-60 parts of silicon dioxide, 10-15 parts of boron oxide, 2-3 parts of aluminum oxide, 6-8 parts of alkali metal oxide, 3-4 parts of composite clarifier and 1-3 parts of modified colorant; The preparation method of the modified colorant comprises the following steps: S1: The cobalt blue material is wrapped by mesoporous silica to obtain a composite material; S2: combining the composite material with a silane coupling agent to obtain a silanized composite material; S3: Combining the silanized composite material with a borate ester to obtain a modified colorant.

[0007] Furthermore, step S1 is specifically as follows: The cobalt blue material is added to an ethanol solution and a concentrated ammonia solution, and ultrasonically treated for 1-1.5 hours to obtain component A, hexadecyltrimethylammonium bromide is added to the ethanol solution to obtain component B, component B is added to component A, and mixed evenly, and then tetraethyl orthosilicate is added, and stirred for 5.5-6.5 hours, centrifuged for 5-10 minutes, washed with deionized water, and finally dried at 80-90°C, and calcined at 450-550°C to obtain a composite material.

[0008] During the above reaction process, tetraethyl orthosilicate and hexadecyltrimethylammonium bromide are combined to form mesoporous silica, and the cobalt blue material is evenly wrapped in the mesoporous silica, and finally a composite material is obtained.

[0009] Furthermore, the mass ratio of the cobalt blue material, the ethanol solution and the concentrated ammonia solution is 0.08-0.12:55-65:1-1.5.

[0010] Furthermore, the mass ratio of the hexadecyltrimethylammonium bromide to the ethanol solution is 0.25-0.35:90-110.

[0011] Furthermore, the preparation method of the cobalt blue material comprises the following steps: Mix the soluble cobalt salt and the soluble aluminum salt evenly, then add a surfactant and deionized water, and stir at room temperature for 10-20 minutes, then add sodium hydroxide solution, and adjust the pH value of the system to 9-11 to obtain a precursor solution, pour the precursor solution into a reactor, and then carry out a hydrothermal reaction. After the reaction is completed, take out the product and cool it to room temperature, then wash it with deionized water, and finally vacuum dry it at 75-85°C to obtain a cobalt blue material.

[0012] Furthermore, the mass ratio of the soluble cobalt salt, the soluble aluminum salt, the surfactant, and the deionized water is 0.8-1.2:1.8-2.2:3-4:25-35.

[0013] Furthermore, the soluble cobalt salt is cobalt chloride; and the soluble aluminum salt is aluminum chloride.

[0014] Furthermore, the surfactant is composed of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide and polyethylene glycol in a mass ratio of 0.7-0.8:0.5-0.6:0.2-0.3.

[0015] Furthermore, in the hydrothermal reaction, the hydrothermal temperature is 240-250° C. and the hydrothermal time is 22-24 h.

[0016] Furthermore, step S2 is specifically as follows: The composite material in step S1 is added to anhydrous toluene and mixed evenly, then the temperature is raised to 110-120°C, a silane coupling agent is added, and a condensation reflux reaction is performed for 8-10 hours. After the reaction is completed, it is cooled to room temperature, washed with anhydrous toluene and anhydrous methanol in turn, and finally dried at 85-95°C to obtain a silanized composite material.

[0017] During the above reaction process, the composite material has a large number of hydroxyl groups on its surface. The silane coupling agent has silanol groups after hydrolysis, which can combine with the hydroxyl groups in the composite material, thereby grafting the silane coupling agent to the surface of the composite material, and finally obtaining a silanized composite material.

[0018] Furthermore, the mass ratio of the composite material, anhydrous toluene and silane coupling agent is 4.5-5.5:90-110:3-4.

[0019] Furthermore, the silane coupling agent is composed of KH550 and KH560 mixed in a mass ratio of 0.8-0.9:0.3-0.4.

[0020] Furthermore, step S3 is specifically as follows: The silanized composite material in step S2 is mixed evenly with the boric acid ester, and then stirred at 90-100° C. for 2-4 hours. After the reaction is completed, centrifugation is performed for 5-10 minutes, and finally drying is performed at 80-90° C. to obtain a modified colorant.

[0021] In the above reaction process, the silylated composite material has an amino group, and the borate contains a boron atom. The amino group in the silylated composite material can combine with the boron atom in the borate to form a complex. The silylated composite material and the borate are combined together to finally obtain a modified colorant.

[0022] Furthermore, the mass ratio of the silanized composite material to the borate ester is 1-2:10-15.

[0023] Furthermore, the borate ester is composed of triisopropyl borate and tributyl borate mixed in a mass ratio of 0.6-0.7:0.4-0.5.

[0024] A method for preparing blue high borosilicate glass comprises the following steps: A1: Weigh the raw materials by mass, mix silicon dioxide, boron oxide, aluminum oxide, alkali metal oxide, composite clarifier and modified colorant evenly, and ball mill for 1-2 hours to obtain powder A; A2: The powder A in step A1 is fed into a melting furnace for high temperature melting for 2-3 hours to obtain glass liquid B; A3: The glass liquid B in step A2 is clarified and homogenized before flowing into the molding mold. The clarification and homogenization temperature is 1450-1550°C; A4: After being clarified and homogenized, the glass liquid B flows into the molding mold and then enters the annealing furnace. The annealing time is 2-4 hours, and then it is cooled at a cooling rate of 4-6℃ / min. After 1.5-2.5 hours, it is cooled to room temperature at a cooling rate of 7-10℃ / min, and finally a blue high borosilicate glass is obtained.

[0025] Furthermore, in step A1, the alkali metal oxide is sodium oxide or potassium oxide.

[0026] Furthermore, in step A1, the composite clarifier is composed of cerium dioxide, sodium sulfate and tin oxide mixed in a mass ratio of 1-1.2:0.6-0.7:0.2-0.3.

[0027] Furthermore, in step A2, the melting temperature is 1600-1700°C.

[0028] Furthermore, in step A4, the annealing temperature is 550-650°C.

[0029] Beneficial effects of the present invention: (1) In the technical scheme of the present invention, a composite material is obtained by wrapping a cobalt blue material with mesoporous silica; the cobalt blue material is synthesized from cobalt chloride, aluminum chloride and a surfactant by a hydrothermal method, and the synthesized cobalt blue material presents a blue color. Wrapping the cobalt blue material with mesoporous silica can not only prevent the volatilization of the cobalt blue material during high-temperature calcination, but also make the color of the high borosilicate glass more uniform and more stable. At the same time, the mesoporous silica can also increase the content of silica in the high borosilicate glass component and further enhance the mechanical properties and thermal stability of the high borosilicate glass; the composite material is combined with a silane coupling agent to obtain a silanized composite material; the surface of the composite material has a large number of hydroxyl groups, which provides more reaction sites, and then the silane coupling agent is grafted onto the surface of the composite material, which can not only improve the dispersibility of the composite material, but also increase its affinity with other components in the high borosilicate glass. The invention discloses a novel nanostructured carbon fiber composite material, wherein the nanostructured carbon fiber has a good compatibility with the nanostructured carbon fiber, and the amino group in the silane coupling agent can provide a reaction site for the subsequent reaction; the silylated composite material is combined with a borate ester to obtain a modified colorant; the borate ester is composed of a mixture of triisopropyl borate and tributyl borate, both of which contain boron and have good heat resistance, which can not only enhance the heat resistance and stability of high borosilicate glass, but also increase the boron content in the high borosilicate glass component and reduce the volatilization of boron, while reducing the production cost; the borate ester is combined with the silylated composite material to improve the bonding force between the composite material and the borate ester, and further enhance the mechanical properties, heat resistance and stability of the high borosilicate glass; the prepared modified colorant can not only make the high borosilicate glass appear blue, but also has stable color under high temperature and high pressure conditions, is not easy to fade, is not easy to volatilize, has high color fastness, and further improves the heat resistance, mechanical properties and stability of the high borosilicate glass.

[0030] (2) In the technical solution of the present invention, silicon dioxide, boron oxide, aluminum oxide, alkali metal oxide, composite clarifier and modified colorant are mixed, ball milled, melted at high temperature, clarified and homogenized, annealed and cooled to obtain blue high borosilicate glass; the added composite clarifier is composed of cerium dioxide, sodium sulfate and tin oxide, and cerium dioxide, sodium sulfate and tin oxide have a synergistic effect, so that the glass has a better clarification effect, improves the clarity of the glass, and can eliminate tiny bubbles in the glass, improve the transparency and appearance quality of the glass, and can also effectively reduce the volatilization of boron and improve the stability of boron; adding alkali metal oxide can further improve the thermal properties and chemical stability of the glass; the finally prepared blue high borosilicate glass has good stability and mechanical properties, and at the same time reduces the content of silicon dioxide and boron in the glass components, reduces the production cost, and improves the quality of the high borosilicate glass. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The specific parameters of the raw materials used in the present invention are as follows: KH550 (γ-aminopropyltriethoxysilane), CAS No.: 919-30-2, provided by Shanghai Titan Technology Co., Ltd.; KH560 (γ-glycidyloxypropyltrimethoxysilane), CAS No.: 2530-83-8, product No.: G810441, provided by Shanghai MacLean Biochemical Technology Co., Ltd.; triisopropyl borate, CAS No.: 5419-55-6, provided by Shanghai MacLean Biochemical Technology Co., Ltd.; tributyl borate, CAS No.: 688-74-4, provided by Shanghai MacLean Biochemical Technology Co., Ltd.; cerium dioxide, provided by Hubei Xingyan New Materials Technology Co., Ltd.; sodium sulfate, CAS No.: 7757-82-6, provided by Shanghai MacLean Biochemical Technology Co., Ltd.; tin oxide, CAS No.: 18282-10-5, product No.: T817640, provided by Shanghai MacLean Biochemical Technology Co., Ltd.

[0033] Example 1 The preparation method of the modified colorant comprises the following steps: S1: According to the mass ratio of cobalt blue material, ethanol solution and concentrated ammonia solution of 0.08:55:1, the cobalt blue material is added to the ethanol solution and 28wt% concentrated ammonia solution, and ultrasonic treatment is carried out at room temperature for 1h (ultrasonic power is 100W, ultrasonic frequency is 40kHz) to obtain component A, according to the mass ratio of hexadecyltrimethylammonium bromide and ethanol solution of 0.25:90, hexadecyltrimethylammonium bromide is added to the ethanol solution to obtain component B, according to the mass ratio of component B to component A of 2:1, component B is added to component A, and mixed evenly, and then tetraethyl orthosilicate is added (the mass of tetraethyl orthosilicate is 40% of the mass of concentrated ammonia solution), and stirred for 5.5h, centrifuged at a speed of 3500rpm for 10min, washed with deionized water 3 times (the mass of deionized water each time is 10 times the mass of concentrated ammonia solution), and finally dried at 80℃ for 11h, and calcined at 450℃ for 4h to obtain a composite material; Wherein, the preparation method of cobalt blue material comprises the following steps: According to the mass ratio of cobalt chloride, aluminum chloride, surfactant and deionized water being 0.8:1.8:3:25, cobalt chloride and aluminum chloride are mixed evenly, and then surfactant and deionized water are added, and stirred at room temperature for 10 minutes, and then 3 mol / L sodium hydroxide solution is added, and the pH value of the system is adjusted to 9 to obtain a precursor solution, and the precursor solution is poured into a reactor, and then a hydrothermal reaction is carried out, the hydrothermal temperature is 240°C, and the hydrothermal time is 22 hours. After the reaction is completed, the product is taken out and cooled to room temperature, and then washed with deionized water 3 times (the mass of deionized water each time is 40% of the mass of the above deionized water), and finally vacuum dried at 75°C for 24 hours to obtain a cobalt blue material, wherein the surfactant is composed of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide and polyethylene glycol mixed in a mass ratio of 0.7:0.5:0.2; S2: According to the mass ratio of composite material, anhydrous toluene and silane coupling agent being 4.5:90:3, the composite material in step S1 is added to anhydrous toluene and mixed evenly, then the temperature is raised to 110°C, and the silane coupling agent is added, and the reaction is condensed and refluxed for 8 hours. After the reaction is completed, it is cooled to room temperature, washed with anhydrous toluene and anhydrous methanol for 3 times each (the mass of anhydrous toluene each time is 2 times the mass of the composite material, and the mass of anhydrous ethanol each time is 3 times the mass of the composite material), and finally dried at 85°C for 24 hours to obtain a silanized composite material, wherein the silane coupling agent is composed of KH550 and KH560 mixed in a mass ratio of 0.8:0.3; S3: According to the mass ratio of the silanized composite material to the borate ester being 1:10, the silanized composite material in step S2 is uniformly mixed with the borate ester, and then stirred for reaction at 90°C for 2h. After the reaction is completed, centrifugation is performed at a speed of 3000rpm for 10min, and finally dried at 80°C for 24h to obtain a modified colorant, wherein the borate ester is composed of triisopropyl borate and tributyl borate mixed at a mass ratio of 0.6:0.4; A blue high borosilicate glass comprises the following raw materials in parts by weight: 50 parts of silicon dioxide, 10 parts of boron oxide, 2 parts of aluminum oxide, 6 parts of sodium oxide, 3 parts of a composite clarifier and 1 part of a modified colorant; The preparation method of blue high borosilicate glass comprises the following steps: A1: Weigh the raw materials by mass, mix silicon dioxide, boron oxide, aluminum oxide, sodium oxide, a composite clarifier and a modified colorant evenly, and perform ball milling for 1 hour to obtain powder A, wherein the composite clarifier is composed of cerium dioxide, sodium sulfate and tin oxide mixed in a mass ratio of 1:0.6:0.2; A2: The powder A in step A1 is fed into a melting furnace for high-temperature melting at a temperature of 1600°C for 3 hours to obtain glass liquid B; A3: The glass liquid B in step A2 is clarified and homogenized before flowing into the forming mold, and the clarification and homogenization temperature is 1450°C; A4: After clarification and homogenization, the glass liquid B flows into the molding mold and then into the annealing furnace. The annealing temperature is 550℃, the annealing time is 4h, and then it is cooled at a cooling rate of 4℃ / min. After 1.5h, it is cooled to room temperature at a cooling rate of 7℃ / min, and finally a blue high borosilicate glass is obtained.

[0034] Example 2 The preparation method of the modified colorant comprises the following steps: S1: According to the mass ratio of cobalt blue material, ethanol solution and concentrated ammonia solution of 0.1:60:1.2, the cobalt blue material is added to the ethanol solution and 28wt% concentrated ammonia solution, and ultrasonic treatment is carried out at room temperature for 1.2h (ultrasonic power is 100W, ultrasonic frequency is 40kHz) to obtain component A, according to the mass ratio of hexadecyltrimethylammonium bromide and ethanol solution of 0.3:100, hexadecyltrimethylammonium bromide is added to the ethanol solution to obtain component B, according to the mass ratio of component B to component A of 2:1, component B is added to component A, and mixed evenly, and then tetraethyl orthosilicate is added (the mass of tetraethyl orthosilicate is 40% of the mass of concentrated ammonia solution), and stirred for 6h, centrifuged at a speed of 4000rpm for 8min, washed with deionized water 3 times (the mass of deionized water each time is 10 times the mass of concentrated ammonia solution), and finally dried at 85°C for 12h, and calcined at 500°C for 3h to obtain a composite material; Wherein, the preparation method of cobalt blue material comprises the following steps: According to the mass ratio of cobalt chloride, aluminum chloride, surfactant and deionized water being 1:2:3.5:30, cobalt chloride and aluminum chloride are mixed evenly, and then surfactant and deionized water are added, and stirred at room temperature for 15 minutes, and then 3 mol / L sodium hydroxide solution is added, and the pH value of the system is adjusted to 10 to obtain a precursor solution, and the precursor solution is poured into a reactor, and then a hydrothermal reaction is carried out, the hydrothermal temperature is 245°C, and the hydrothermal time is 23 hours. After the reaction is completed, the product is taken out and cooled to room temperature, and then washed with deionized water 3 times (the mass of deionized water each time is 40% of the mass of the above deionized water), and finally vacuum dried at 80°C for 24 hours to obtain a cobalt blue material, wherein the surfactant is composed of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide and polyethylene glycol mixed in a mass ratio of 0.75:0.55:0.25; S2: According to the mass ratio of composite material, anhydrous toluene and silane coupling agent being 5:100:3.5, the composite material in step S1 is added to anhydrous toluene and mixed evenly, then the temperature is raised to 115°C, and the silane coupling agent is added, and the reaction is condensed and refluxed for 9 hours. After the reaction is completed, it is cooled to room temperature, washed with anhydrous toluene and anhydrous methanol for 4 times respectively (the mass of anhydrous toluene each time is 2 times the mass of the composite material, and the mass of anhydrous ethanol each time is 3 times the mass of the composite material), and finally dried at 90°C for 24 hours to obtain a silanized composite material, wherein the silane coupling agent is composed of KH550 and KH560 mixed in a mass ratio of 0.85:0.35; S3: According to the mass ratio of the silanized composite material to the boric acid ester being 1.5:12, the silanized composite material and the boric acid ester in step S2 are uniformly mixed, and then stirred for reaction at 95°C for 3 hours. After the reaction is completed, centrifugation is performed at a speed of 3500 rpm for 8 minutes, and finally dried at 85°C for 24 hours to obtain a modified colorant, wherein the boric acid ester is composed of triisopropyl borate and tributyl borate mixed in a mass ratio of 0.65:0.45; A blue high borosilicate glass comprises the following raw materials in parts by weight: 55 parts of silicon dioxide, 12 parts of boron oxide, 2.5 parts of aluminum oxide, 7 parts of potassium oxide, 3.5 parts of a composite clarifier and 2 parts of a modified colorant; The preparation method of blue high borosilicate glass comprises the following steps: A1: Weigh the raw materials by mass, mix silicon dioxide, boron oxide, aluminum oxide, potassium oxide, composite clarifier and modified colorant evenly, and perform ball milling for 1.5 hours to obtain powder A, wherein the composite clarifier is composed of cerium dioxide, sodium sulfate and tin oxide mixed in a mass ratio of 1.1:0.65:0.25; A2: The powder A in step A1 is fed into a melting furnace for high-temperature melting at a temperature of 1650°C for a melting time of 2.5 hours to obtain glass liquid B; A3: The glass liquid B in step A2 is clarified and homogenized and then flows into the forming mold, and the clarification and homogenization temperature is 1500°C; A4: After clarification and homogenization, the glass liquid B flows into the molding mold and then into the annealing furnace. The annealing temperature is 600℃, the annealing time is 3h, and then it is cooled at a cooling rate of 5℃ / min. After 2h, it is cooled to room temperature at a cooling rate of 8℃ / min, and finally a blue high borosilicate glass is obtained.

[0035] Example 3 The preparation method of the modified colorant comprises the following steps: S1: According to the mass ratio of cobalt blue material, ethanol solution and concentrated ammonia solution of 0.12:65:1.5, the cobalt blue material is added to the ethanol solution and 28wt% concentrated ammonia solution, and ultrasonic treatment is carried out at room temperature for 1.5h (ultrasonic power is 100W, ultrasonic frequency is 40kHz) to obtain component A, according to the mass ratio of hexadecyltrimethylammonium bromide and ethanol solution of 0.35:110, hexadecyltrimethylammonium bromide is added to the ethanol solution to obtain component B, according to the mass ratio of component B to component A of 2:1, component B is added to component A, and mixed evenly, and then tetraethyl orthosilicate is added (the mass of tetraethyl orthosilicate is 40% of the mass of concentrated ammonia solution), and stirred for 6.5h, centrifuged at a speed of 4500rpm for 5min, washed with deionized water 3 times (the mass of deionized water each time is 10 times the mass of concentrated ammonia solution), and finally dried at 90°C for 13h, and calcined at 550°C for 2h to obtain a composite material; Wherein, the preparation method of cobalt blue material comprises the following steps: According to the mass ratio of cobalt chloride, aluminum chloride, surfactant and deionized water being 1.2:2.2:4:35, cobalt chloride and aluminum chloride are mixed evenly, and then surfactant and deionized water are added, and stirred at room temperature for 20 minutes, and then 3 mol / L sodium hydroxide solution is added, and the pH value of the system is adjusted to 11 to obtain a precursor solution, and the precursor solution is poured into a reactor, and then a hydrothermal reaction is carried out, the hydrothermal temperature is 250°C, and the hydrothermal time is 24 hours. After the reaction is completed, the product is taken out and cooled to room temperature, and then washed with deionized water 3 times (the mass of deionized water each time is 40% of the mass of the above deionized water), and finally vacuum dried at 85°C for 24 hours to obtain a cobalt blue material, wherein the surfactant is composed of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide and polyethylene glycol mixed in a mass ratio of 0.8:0.6:0.3; S2: According to the mass ratio of composite material, anhydrous toluene and silane coupling agent being 5.5:110:4, the composite material in step S1 is added to anhydrous toluene and mixed evenly, then the temperature is raised to 120°C, and the silane coupling agent is added, and the reaction is condensed and refluxed for 10 hours. After the reaction is completed, it is cooled to room temperature, washed with anhydrous toluene and anhydrous methanol for 5 times each (the mass of anhydrous toluene each time is 2 times the mass of the composite material, and the mass of anhydrous ethanol each time is 3 times the mass of the composite material), and finally dried at 95°C for 24 hours to obtain a silanized composite material, wherein the silane coupling agent is composed of KH550 and KH560 mixed in a mass ratio of 0.9:0.4; S3: according to the mass ratio of the silanized composite material to the borate ester being 2:15, the silanized composite material in step S2 is uniformly mixed with the borate ester, and then stirred for reaction at 100°C for 4 hours. After the reaction is completed, centrifugation is performed at a speed of 4000 rpm for 5 minutes, and finally dried at 90°C for 24 hours to obtain a modified colorant, wherein the borate ester is composed of triisopropyl borate and tributyl borate mixed at a mass ratio of 0.7:0.5; A blue high borosilicate glass comprises the following raw materials in parts by weight: 60 parts of silicon dioxide, 15 parts of boron oxide, 3 parts of aluminum oxide, 8 parts of sodium oxide, 4 parts of a composite clarifier and 3 parts of a modified colorant; The preparation method of blue high borosilicate glass comprises the following steps: A1: Weigh the raw materials by mass, mix silicon dioxide, boron oxide, aluminum oxide, sodium oxide, a composite clarifier and a modified colorant evenly, and perform ball milling for 2 hours to obtain powder A, wherein the composite clarifier is composed of cerium dioxide, sodium sulfate and tin oxide mixed in a mass ratio of 1.2:0.7:0.3; A2: The powder A in step A1 is fed into a melting furnace for high-temperature melting at a temperature of 1700°C for 2 hours to obtain glass liquid B; A3: The glass liquid B in step A2 is clarified and homogenized before flowing into the molding mold, and the clarification and homogenization temperature is 1550°C; A4: After clarification and homogenization, the glass liquid B flows into the molding mold and then into the annealing furnace. The annealing temperature is 650℃, the annealing time is 2h, and then it is cooled at a cooling rate of 6℃ / min. After 2.5h, it is cooled to room temperature at a cooling rate of 10℃ / min, and finally a blue high borosilicate glass is obtained.

[0036] Comparative Example 1 The difference between this comparative example and Example 3 is that when preparing the modified colorant, the mass of cobalt chloride and aluminum chloride in step S1 is replaced by cobalt nitrate and aluminum nitrate, and the remaining steps and raw materials are the same as those in Example 3; The preparation method of cobalt blue material comprises the following steps: According to the mass ratio of cobalt nitrate, aluminum nitrate, surfactant and deionized water of 1.2:2.2:4:35, cobalt nitrate and aluminum nitrate are evenly mixed, and then surfactant and deionized water are added, and stirred at room temperature for 20 minutes, and then 3 mol / L sodium hydroxide solution is added, and the pH value of the system is adjusted to 11 to obtain a precursor solution, the precursor solution is poured into a reactor, and then a hydrothermal reaction is carried out at a hydrothermal temperature of 250°C and a hydrothermal time of 24 hours. After the reaction is completed, the product is taken out and cooled to room temperature, and then washed with deionized water 3 times (the mass of deionized water each time is 40% of the mass of the above deionized water), and finally vacuum dried at 85°C for 24 hours to obtain a cobalt blue material, wherein the surfactant is composed of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide and polyethylene glycol mixed in a mass ratio of 0.8:0.6:0.3.

[0037] Comparative Example 2 The difference between this comparative example and Example 3 is that, when preparing the modified colorant, the cobalt blue material in step S1 is coated with silicon dioxide, and the remaining steps and raw materials are the same as those in Example 3; S1: According to the mass ratio of cobalt blue material, ethanol solution and concentrated ammonia solution of 0.12:65:1.5, the cobalt blue material was added to the ethanol solution and 28wt% concentrated ammonia solution, and ultrasonically treated at room temperature for 1.5h (ultrasonic power of 100W, ultrasonic frequency of 40kHz), and then tetraethyl orthosilicate was added (the mass of tetraethyl orthosilicate was 40% of the mass of concentrated ammonia solution), and stirred for 6.5h, centrifuged at 4500rpm for 5min, washed with deionized water for 3 times (the mass of deionized water each time was 10 times the mass of concentrated ammonia solution), and finally dried at 90℃ for 13h, and calcined at 550℃ for 2h to obtain a composite material.

[0038] Comparative Example 3 The difference between this comparative example and Example 3 is that when preparing the modified colorant, the mass of the boric acid ester in step S3 is replaced by triisopropyl borate, and the remaining steps and raw materials are the same as those in Example 3; S3: According to the mass ratio of the silanized composite material to triisopropyl borate of 2:15, the silanized composite material in step S2 is evenly mixed with triisopropyl borate, and then stirred for reaction at 100°C for 4 hours. After the reaction is completed, centrifuge at a speed of 4000 rpm for 5 minutes, and finally dry at 90°C for 24 hours to obtain a modified colorant.

[0039] Comparative Example 4 The difference between this comparative example and Example 3 is that when preparing the modified colorant, the mass of the boric acid ester in step S3 is replaced by tributyl borate, and the remaining steps and raw materials are the same as those in Example 3; S3: According to the mass ratio of the silanized composite material to tributyl borate of 2:15, the silanized composite material in step S2 is evenly mixed with tributyl borate, and then stirred for reaction at 100°C for 4 hours. After the reaction is completed, centrifuge at a speed of 4000 rpm for 5 minutes, and finally dry at 90°C for 24 hours to obtain a modified colorant.

[0040] Comparative Example 5 The difference between this comparative example and Example 3 is that when preparing blue high borosilicate glass, the modified colorant in step A1 is replaced by cobalt oxide, the preparation step of the modified colorant is deleted, and the remaining steps and raw materials are the same as those in Example 3; A blue high borosilicate glass comprises the following raw materials in parts by weight: 60 parts of silicon dioxide, 15 parts of boron oxide, 3 parts of aluminum oxide, 8 parts of sodium oxide, 4 parts of a composite clarifier and 3 parts of cobalt oxide; The preparation method of blue high borosilicate glass comprises the following steps: A1: Weigh the raw materials in parts by mass, mix silicon dioxide, boron oxide, aluminum oxide, sodium oxide, a composite clarifier and cobalt oxide evenly, and perform ball milling for 2 hours to obtain powder A, wherein the composite clarifier is composed of cerium dioxide, sodium sulfate and tin oxide mixed in a mass ratio of 1.2:0.7:0.3.

[0041] Comparative Example 6 The difference between this comparative example and Example 3 is that when preparing blue high borosilicate glass, the composite clarifier in step A1 is composed of cerium dioxide and sodium sulfate mixed in a mass ratio of 1.2:1, and the remaining steps and raw materials are the same as those in Example 3; A1: Weigh the raw materials by mass, mix silicon dioxide, boron oxide, aluminum oxide, sodium oxide, a composite clarifier and a modified colorant evenly, and perform ball milling for 2 hours to obtain powder A, wherein the composite clarifier is composed of cerium dioxide and sodium sulfate mixed in a mass ratio of 1.2:1.

[0042] Comparative Example 7 The difference between this comparative example and Example 3 is that when preparing blue high borosilicate glass, the composite clarifier in step A1 is composed of cerium dioxide and tin oxide mixed in a mass ratio of 1.2:1, and the remaining steps and raw materials are the same as those in Example 3; A1: Weigh the raw materials by mass, mix silicon dioxide, boron oxide, aluminum oxide, sodium oxide, a composite clarifier and a modified colorant evenly, and perform ball milling for 2 hours to obtain powder A, wherein the composite clarifier is composed of cerium dioxide and tin oxide mixed in a mass ratio of 1.2:1.

[0043] Comparative Example 8 The difference between this comparative example and Example 3 is that when preparing blue high borosilicate glass, the composite clarifier in step A1 is composed of sodium sulfate and tin oxide mixed in a mass ratio of 1.2:1, and the remaining steps and raw materials are the same as those in Example 3; A1: Weigh the raw materials by mass, mix silicon dioxide, boron oxide, aluminum oxide, sodium oxide, a composite clarifier and a modified colorant evenly, and perform ball milling for 2 hours to obtain powder A, wherein the composite clarifier is composed of sodium sulfate and tin oxide mixed in a mass ratio of 1.2:1.

[0044] The blue high borosilicate glass prepared in Examples 1-3 and Comparative Examples 1-8 is now tested for bending strength, boron volatilization rate, bubble degree and optical uniformity. The bending strength test method is as follows: the blue high borosilicate glass prepared in Examples 1-3 and Comparative Examples 1-8 is made into a number of glass samples with a length of 120 mm, a width of 20 mm and a thickness of 5 mm. A bending test is performed on a testing machine according to the bending strength test method for glass materials published in "JC / T676-1997". The bending strength of the high borosilicate glass sample is obtained by calculating the maximum complete stress at the cross section under load. The bending strength of the glass sample is obtained by averaging the results of repeated bending tests. The boron content is measured according to "GBZ / T 160.27-2004" to determine the boron volatilization rate. The bubble degree is tested according to the "GB / T 7962.8-2010" standard. The optical uniformity is tested according to the "GB / T 7962.3-2010" standard. The test results are shown in Table 1 below: Table 1 Performance parameters of blue high borosilicate glass prepared in Examples 1-3 and Comparative Examples 1-8

[0045] It can be seen from the data in Table 1 above that, by comparing Comparative Examples 1-2 with Example 3, it can be seen that the mass of cobalt chloride and aluminum chloride in step S1 is replaced with cobalt nitrate and aluminum nitrate, or the cobalt blue material in step S1 is coated with silica to prepare a modified colorant, and its test results are worse than those of Example 3, indicating that the cobalt blue material synthesized by a hydrothermal method using cobalt chloride and aluminum chloride can present a better blue color, which can not only increase the blue effect and uniformity of high borosilicate glass, but also make the blue color of high borosilicate glass more stable, not easy to volatilize and fade, and can effectively reduce the volatilization of boron in the glass; by wrapping the cobalt blue material with mesoporous silica, the stability of the cobalt blue material can be increased, making it not easy to volatilize, and reducing the volatilization of boron in the glass, further improving the mechanical properties and stability of the high borosilicate glass; By comparing Comparative Examples 3-4 with Example 3, it can be seen that the mass of the borate ester in step S3 is replaced by triisopropyl borate or tributyl borate, and the modified colorant is finally prepared. The test result is worse than that of Example 3, indicating that the borate ester composed of a mixture of triisopropyl borate and tributyl borate can not only improve the heat resistance and stability of the glass, but also increase the boron content in the glass component, further enhance the mechanical properties and stability of the high borosilicate glass, and reduce the volatilization of boron, so that the blue color of the high borosilicate glass is more uniform, and the quality of the high borosilicate glass is effectively improved; By comparing Comparative Examples 5-8 with Example 3, it can be seen that the modified colorant in step A1 is replaced with cobalt oxide, or the composite clarifier is composed of a mixture of cerium dioxide and sodium sulfate, or the composite clarifier is composed of a mixture of cerium dioxide and tin oxide, or the composite clarifier is composed of a mixture of sodium sulfate and tin oxide to prepare blue high borosilicate glass, and the test results are worse than those of Example 3, indicating that the blue high borosilicate glass prepared by mixing the modified colorant with other glass raw materials effectively improves the mechanical properties and stability of the high borosilicate glass, reduces the volatilization of boron and the generation of bubbles, increases its optical uniformity, and makes its coloring more stable and less volatile; the composite clarifier composed of a mixture of cerium dioxide, sodium sulfate and tin oxide can play a synergistic role, improves its clarity during the glass melting process, further improves the mechanical properties of the high borosilicate glass, effectively reduces the volatilization of boron, and ultimately improves the quality of the glass.

[0046] It can be seen from Table 1 above that the blue high borosilicate glass prepared in Example 1-3 is compared with the blue high borosilicate glass prepared in Comparative Example 1-8. The cobalt blue material is wrapped by mesoporous silica, and then combined with a silane coupling agent, and then combined with a borate to obtain a modified colorant. Silica, boron oxide, aluminum oxide, alkali metal oxide, composite clarifier and modified colorant are mixed, ball milled, melted at high temperature, clarified and homogenized, annealed, and cooled to obtain blue high borosilicate glass, which meets the test performance requirements, while the blue high borosilicate glass prepared in Comparative Example 1-8 does not meet the performance requirements. The blue high borosilicate glass prepared by the present invention can not only improve the mechanical properties and stability of the glass, but also effectively reduce the volatilization of boron and the generation of bubbles, increase optical uniformity, and make the high borosilicate glass have a more significant blue color, and the coloring is more stable and durable, not easy to volatilize, thereby improving the quality of the glass.

[0047] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0048] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the present invention, they shall all fall within the protection scope of the present invention.

Claims

1. A blue high borosilicate glass, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of silicon dioxide, 10-15 parts of boron oxide, 2-3 parts of aluminum oxide, 6-8 parts of alkali metal oxide, 3-4 parts of composite clarifier and 1-3 parts of modified colorant; The preparation method of the modified colorant comprises the following steps: S1: The cobalt blue material is wrapped by mesoporous silica to obtain a composite material; S2: combining the composite material with a silane coupling agent to obtain a silanized composite material; S3: Combining the silanized composite material with a borate ester to obtain a modified colorant.

2. The blue high borosilicate glass according to claim 1, characterized in that: Step S1 is specifically as follows: The cobalt blue material is added to an ethanol solution and a concentrated ammonia solution, and ultrasonically treated for 1-1.5 hours to obtain component A, hexadecyltrimethylammonium bromide is added to the ethanol solution to obtain component B, component B is added to component A, and mixed evenly, and then tetraethyl orthosilicate is added, and stirred for 5.5-6.5 hours, centrifuged for 5-10 minutes, washed with deionized water, and finally dried at 80-90°C, and calcined at 450-550°C to obtain a composite material.

3. The blue high borosilicate glass according to claim 2, characterized in that: The preparation method of the cobalt blue material comprises the following steps: Mix the soluble cobalt salt and the soluble aluminum salt evenly, then add a surfactant and deionized water, and stir at room temperature for 10-20 minutes, then add sodium hydroxide solution, and adjust the pH value of the system to 9-11 to obtain a precursor solution, pour the precursor solution into a reactor, and then carry out a hydrothermal reaction. After the reaction is completed, take out the product and cool it to room temperature, then wash it with deionized water, and finally vacuum dry it at 75-85°C to obtain a cobalt blue material.

4. The blue high borosilicate glass according to claim 3, characterized in that: The soluble cobalt salt is cobalt chloride; the soluble aluminum salt is aluminum chloride.

5. The blue high borosilicate glass according to claim 1, characterized in that: Step S2 is specifically as follows: The composite material in step S1 is added to anhydrous toluene and mixed evenly, then the temperature is raised to 110-120°C, a silane coupling agent is added, and a condensation reflux reaction is performed for 8-10 hours. After the reaction is completed, it is cooled to room temperature, washed with anhydrous toluene and anhydrous methanol in turn, and finally dried at 85-95°C to obtain a silanized composite material.

6. The blue high borosilicate glass according to claim 5, characterized in that: The silane coupling agent is composed of KH550 and KH560 mixed in a mass ratio of 0.8-0.9:0.3-0.

4.

7. The blue high borosilicate glass according to claim 1, characterized in that: Step S3 is specifically as follows: The silanized composite material in step S2 is mixed evenly with the boric acid ester, and then stirred at 90-100° C. for 2-4 hours. After the reaction is completed, centrifugation is performed for 5-10 minutes, and finally drying is performed at 80-90° C. to obtain a modified colorant.

8. The blue high borosilicate glass according to claim 7, characterized in that: The boric acid ester is composed of triisopropyl borate and tributyl borate mixed in a mass ratio of 0.6-0.7:0.4-0.

5.

9. The blue high borosilicate glass according to claim 1, characterized in that: The composite clarifier is composed of cerium dioxide, sodium sulfate and tin oxide mixed in a mass ratio of 1-1.2:0.6-0.7:0.2-0.

3.

10. A method for preparing blue high borosilicate glass according to any one of claims 1 to 9, characterized in that: The following steps are involved: A1: Weigh the raw materials by mass, mix silicon dioxide, boron oxide, aluminum oxide, alkali metal oxide, composite clarifier and modified colorant evenly, and ball mill for 1-2 hours to obtain powder A; A2: The powder A in step A1 is fed into a melting furnace for high temperature melting for 2-3 hours to obtain glass liquid B; A3: The glass liquid B in step A2 is clarified and homogenized before flowing into the molding mold. The clarification and homogenization temperature is 1450-1550°C; A4: After being clarified and homogenized, the glass liquid B flows into the molding mold and then enters the annealing furnace. The annealing time is 2-4 hours, and then it is cooled at a cooling rate of 4-6℃ / min. After 1.5-2.5 hours, it is cooled to room temperature at a cooling rate of 7-10℃ / min, and finally a blue high borosilicate glass is obtained.

Citation Information

Patent Citations

  • Blue glass for medical packaging and uses thereof

    CN101428968A

  • Process for preparing spherical nanometer spinel zaffre by hydrothermal method

    CN102241528A

  • Blue high-strength glass and preparation method thereof

    CN115159843A

  • Green jade high borosilicate glass profile and preparation method thereof

    CN118637824A

  • Ceramic fiber and polymer fiber composite reinforced material and preparation method thereof

    CN118927722A

Cited By

  • Colored dry granules and preparation method thereof

    CN121020973A

  • Lightweight high-strength building glass and preparation method thereof

    CN121651698A

  • A lightweight, high-strength architectural glass and its preparation method

    CN121651698B